Eosinophilic cholangitis coexisted with idiopathic thrombocytopenic purpura: Report of a case. Issue 5 (24th July 2014) - Hokuto, Daisuke; Yamato, Ichiro; Nomi, Takeo; Yasuda, Satoshi; Obara, Shinsaku; Yamada, Takatsugu; Chihiro, Kawaguchi; Nakajima, Yoshiyuki
Abstract : Eosinophilic cholangitis is a rare disease of which only 31 cases have been reported. Eosinophilic infiltration causes stricture of the bile duct diffusely or locally, and the imaging of eosinophilic cholangitis resembles primary sclerosing cholangitis or cancer of the bile tract. For eosinophilic cholangitis, treatment with steroid is effective and the prognosis is good. Therefore, its accurate diagnosis is very important. Here, we describe a patient with eosinophilic cholangitis who was also diagnosed with idiopathic thrombocytopenic purpura (ITP). He was treated for ITP using prednisolone, the unexpected sudden interruption of which caused severe deterioration of eosinophilic cholangitis and acute cholecystitis. Cholecystectomy and choledochojejunostomy were performed, and the addition of treatment by prednisolone resulted in a good clinical course. This is the first report on eosinophilic cholangitis coexisting with ITP.